2020
DOI: 10.25122/jml-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Signification of Serum Alpha-Fetoprotein Levels in Cases of Compensated Cirrhosis and Hepatitis C Virus without Hepatocellular Carcinoma

Abstract: AFP (alpha-fetoprotein) levels are increased during the development of HCC (hepatocellular carcinoma); nonetheless, it can also be produced by non-tumoral hepatocytes in conditions of high cell turnover. Our study aims to provide additional data regarding the causes of elevated AFP in patients with liver cirrhosis due to hepatitis C virus (HCV) infection. We conducted an observational prospective cohort study that included 2068 patients with compensated cirrhosis and chronic hepatitis C genotype 1b infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…We also observed a significant difference in the distribution of AST and ALT by viral infection status, and this could be due to acute/chronic (53,54), despite its contested role (55). It may not be an indispensable diagnostic or screening tool (56); however, our study showed that serum AFP levels were markedly elevated. Similarly, GGT has also been proposed as a potential marker for the early detection of HCC.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We also observed a significant difference in the distribution of AST and ALT by viral infection status, and this could be due to acute/chronic (53,54), despite its contested role (55). It may not be an indispensable diagnostic or screening tool (56); however, our study showed that serum AFP levels were markedly elevated. Similarly, GGT has also been proposed as a potential marker for the early detection of HCC.…”
Section: Discussionmentioning
confidence: 60%
“…AFP is a biomarker whose serum concentration rises in most patients with HCC; consequently, it has been utilised in the monitoring and diagnosis of or early detection of neoplasms in HCC (53,54), despite its contested role (55). It may not be an indispensable diagnostic or screening tool (56); however, our study showed that serum AFP levels were markedly elevated. Similarly, GGT has also been proposed as a potential marker for the early detection of HCC.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In the last five years, the treatment of HCV infection has greatly advanced with the introduction of new, more efficient agents named direct-acting antivirals (DAAs) [ 2 ]. These drugs target several nonstructural proteins of the virus that disrupt replication and stop the infection.…”
Section: Introductionmentioning
confidence: 99%